Information and regulation for technology adoption: lessons from Uganda - Gilligan, Daniel O.; Karachiwalla, Naureen (International Food Policy Research Institute, 2021)
Key Messages - Adoption of productivity-enhancing agricultural technology is low, partly because many of these products are of low-quality and because farmers cannot distinguish between high- and low-quality products. Consequently, farmers do not purchase the products and high-quality producers exit markets. - Governments and/or private regulators can create opportunities for farmers to learn about product quality and increase adoption. One option is a product assurance scheme that provides information to farmers about the quality of the product they purchase. - An example comes from the Uganda National Bureau of Standards, which created a product assurance scheme called Kakasa. The scheme led to large increases in the adoption of both glyphosate herbicide and hybrid maize seed, which both participated in the scheme. - Policymakers should consider providing information to farmers about the quality of agricultural inputs. This can be done without a complicated system of testing, and product assurance can generate sustained increases in adoption and become selfsustaining over time when companies contribute to the scheme.